Fire conditions and source materials recorded in scoria from an intentional fire at Store Tovstrup Iron Age house, Central Jutland, Denmark. (October 2018) - Thy, Peter; Barfod, Gry H.; Christensen, Lotte Bach; Hansen, Astrid Skou
Abstract: The composition, mineralogy, and textures preserved in scoria from ancient fires provide constraints on the firing temperature, the source and nature of the fire, and its potential social and cultural implications. Analyses of four scoria fragments preserved in a posthole of an Iron Age longhouse at Store Tovstrup, West Denmark, by scanning electron microscopy, electron microprobe, and laser ablation ICP-MS show these to consist of rounded quartz and orthoclase grains, gas vesicles, and carbonaceous material bonded together by a silicate- and potassium-rich (SiO2 67–69 wt% and K2 O 11–14 wt%) melt (now glass). Given the presence of vesicles and carbonaceous material, the fire is indicated to have occurred under restricted air-flow and to have involved decomposition of biomass and soil. The initiation of melting occurred during what was presumably an event of short duration. Simplified ternary phase equilibria point to localized melting initiated around 700–800 °C and continuing to about 1000 °C. The main structure succumbed to char at lower temperatures. Calculations suggest that a mixture of 50% sandy soil, 41% barley straw, and 9% oak branches best explains the low Al2 O3, Fe2 O3, and Na2 O concentrations in the melt phase. The scoria at Store Tovstrup most likely originated from a short duration burning with restricted air-flow resulting in the collapse and charring of daub walls. The fire was intentional and set after the house had been cleared of household goods. Highlights: Silicate scoria particles were found in a fire debris field after an Iron Age Longhouse Wall melting occurred heterogeneously and locally reached temperatures of 700-1000 °C The scoria composition indicates decomposition and partial melting of a mixture of soil, cereal straw, and oak branches The high temperatures, restricted airflow and the lack of household goods support an intentional fire It is proposed that silicate scoria particles may be more common in fire fields than the literature indicate